Respuesta fisiológica del tomate de árbol (Solanum betaceum Cav.) a diferentes regímenes hídricos y niveles de fertilizante, en un suelo andisol del departamento de Nariño (2020)
One of the main challenges in modern agriculture is to make a more sustainable use of water and plant nutrition. The objective of the research was to evaluate the physiological response of the tree tomato to different water regimes and fertilizer levels in a Vitric Haplustand. Controlled deficit irrigation was used with an experimental design of divided plots, 3x3 factorial arrangement, where the main plot corresponded to fertilizer levels: F1 = 200 g plant-1 (33, 9 and 51 kgha-1 of NPK), F2 = 140 g plant-1 (23, 6 and 36 kgha-1 of NPK) and F3 = 70 g plant-1 (12, 3 and 18 kgha-1 of NPK), the subplots to irrigation sheets 100% ETo, 75% ETo and 50% ETo) and nine treatments that corresponded to the fertilizer interactions (F) per sheet of water (L). The results showed statistical differences where the interaction of fertilizer (140 g plant-1) and the application of the sheet with 50% ETo, significantly affected Ψf in flowering, with values lower than -0.42 MPa, reaching better CUB (37 , 75 and 93 Kgkg-1 of NPK in leaf and 22, 86 and 64 Kgkg-1 of NPK in root), EUN (60, 2.7 and 26 Kgkg-1 of NPK in leaf and 52, 2.4 and 18 Kgkg-1 of NPK at root) and better yield (17 t ha-1 year-1), equatorial diameter (63.2 mm), fruit weight (178.1 g) and SST (10.6 ° Bx), meaning in drought, a saving in water of 51.7% (4,500 m3 ha-1 year-1) and of synthesis fertilizer 200 kg ha-1 year-1.